Editorial - Barbosa, Plínio Almeida (Journal of Speech Sciences, 2021)
his is the third issue (issue 1 of volume 2) of the Journal of Speech Sciences (JoSS). JoSS is an open access journal which follows the principles of the Directory of Open Access Journals (DOAJ), meaning that its readers can freely read, download, copy, distribute, print, search, or link to the full texts of any article electronically published in the journal. All papers are registered in the DOAJ. We fully subscribe to the position of Gideon Burton, Assistant Professor of English at Brigham Young University, cited by Larry Lessig, who said that Open Access “it is the only ethical move available to scholars who take their own work seriously enough to believe its value lies in how well it engages many publics and not just a few peers”. The journal is also indexed in Linguistics Abstracts.